2017
DOI: 10.18203/2320-1770.ijrcog20172304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hormonal and copper IUDs on genital microbial colonisation and clinical outcomes in North-Western Nigeria

Abstract: Background: Intrauterine devices are one of the popular long term reversible contraceptive methods. Earlier forms were associated with genital infections, however more recent types such copper IUDs and hormonal types have been shown to have better safety profile. However, there is no conclusive evidence to demonstrate that hormonal IUD is less associated with genital infection when compared with copper IUDs. The objectives include determination of prevalence of genital tract infections among IUD users, to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…11 But our study is supported by Sharon L Hillier, Michele Austin et al 12 In present study regarding characteristic of discharge, Curdy discharge was present 61.25%, frothy discharge was present 16.25% and homogeneous charge was present in 17.5%. This is supported by the study of Venugopal S, Gopalan K, Devi A, Kavitha A et al 13 In our study lower abdominal pain was most common followed by dysuria and dyspareunia which corroborates with the study of Narayankhedkar A, Hodiwala A, Mane A et al and Saidu AD, Tunau KA, Panti AA, Nwobodo EI, Mohammed Y, Amin J, et al 14,15 Regarding clinical finding in patients changes in vulva was most common clinical finding followed by vaginal erythema and cervical changes. In most of the patient the discharge was purulent and in 30 5 patients it was profuse.…”
Section: Discussionsupporting
confidence: 90%
“…11 But our study is supported by Sharon L Hillier, Michele Austin et al 12 In present study regarding characteristic of discharge, Curdy discharge was present 61.25%, frothy discharge was present 16.25% and homogeneous charge was present in 17.5%. This is supported by the study of Venugopal S, Gopalan K, Devi A, Kavitha A et al 13 In our study lower abdominal pain was most common followed by dysuria and dyspareunia which corroborates with the study of Narayankhedkar A, Hodiwala A, Mane A et al and Saidu AD, Tunau KA, Panti AA, Nwobodo EI, Mohammed Y, Amin J, et al 14,15 Regarding clinical finding in patients changes in vulva was most common clinical finding followed by vaginal erythema and cervical changes. In most of the patient the discharge was purulent and in 30 5 patients it was profuse.…”
Section: Discussionsupporting
confidence: 90%
“…Madden et al (2012) found the incidence of BV was 37.0% among IUD users and 19.3% in combined oral contraceptives, ring and patch users. 22 Joesoef MR et al, found the prevalence of bacterial vaginosis in 47.2% of cases of IUD users and 26.6% in cases of other hormonal contraceptive users. 23 In this study 25.6% cases with bacterial vaginosis were pregnant.…”
Section: Resultsmentioning
confidence: 98%
“…During IUD use, IUD has been colonized by anaerobic and aerobic bacteria and change the genital tract microbiota, which then may increase the prevalence of genital tract infection [7][8][9]. 9% of the bacterial species that human body hosts are associated with the urogenital tract [10].…”
Section: Introductionmentioning
confidence: 99%